The effect of novel compounds on cell survival and apoptosis in colon cancer cell lines - Dahan-Farkas, Nurit (My University, 2013)
Colon cancer is the third most common cancer worldwide and the second most common in the western world. More than 40 % of colon cancer sufferers develop metastases and chemotherapy is often used alone or in combination with radiotherapy as adjunctive therapy for the advanced disease. A major effort has been made in the past decade to develop anticancer agents through both empiric screening and rational design of new compounds. These attempts are made to improve the survival rate, reduce the severe adverse effects associated with existing cancer chemotherapeutic agents as well as to reduce the development of drug resistance. In the present study, two colon cancer cell lines were exposed to novel imidazo[1,2-a]pyridines and novel nucleoside analogues, aiming to investigate the cytotoxic efficacy on the cells, the mode of cell death, and to explore the pathways by which cell death was induced.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Masters of Science in Medicine (Pharmacology) Johannesburg, 2013
Keywords: Colonic Neoplasms--drug therapy